2018
DOI: 10.1016/j.vaccine.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Epitope selection and their placement for increased virus neutralization in a novel vaccination strategy for porcine epidemic diarrhea virus utilizing the Hepatitis B virus core antigen

Abstract: Porcine epidemic diarrhea virus (PEDV) is a member of the Alphacoronaviridae genus within the Coronaviridae family. It is the causative agent of porcine epidemic diarrhea, a disease that can have mortality rates as high as 100% in suckling piglets. PEDV causes severe economic loss, and has been in existence for decades. A panzootic starting in 2010 renewed interest in the development of a universal vaccine toward PEDV. This report details several design changes made to a Hepatitis B virus core antigen (HBcAg)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The foreign peptide is typically introduced genetically into the VLP at the N-terminus, C-terminus, or preferably in the major immunodominant region (MIR) (Karpenko et al, 2000;Pumpens and Grens, 2001). However, insertion of a foreign epitope often results in insoluble, misassembled or aggregated capsids, lacking the desired immunogenicity (Karpenko et al, 2000;Billaud et al, 2005;Gillam and Zhang, 2018). The process of identifying soluble cVLP constructs is highly empirical and time-consuming (Chackerian, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The foreign peptide is typically introduced genetically into the VLP at the N-terminus, C-terminus, or preferably in the major immunodominant region (MIR) (Karpenko et al, 2000;Pumpens and Grens, 2001). However, insertion of a foreign epitope often results in insoluble, misassembled or aggregated capsids, lacking the desired immunogenicity (Karpenko et al, 2000;Billaud et al, 2005;Gillam and Zhang, 2018). The process of identifying soluble cVLP constructs is highly empirical and time-consuming (Chackerian, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More interesting, however, is the positive effect that increasing hapten density has had on the occurrence of CIES, presumably through the crowding of carrier-specific BCR epitopes (138). Interruption, removal, or blocking of AIRs in chimeric VLP formulations via recombinant and/or chemical means has been shown to improve immunogenicity toward target epitopes and minimize immunogenicity toward carrier protein, further corroborating this presumption (122,139,140). However, chemical modification, such as PEGylation, is largely non-specific, thus resulting in unpredictable outcomes for vaccines.…”
Section: Carrier Induced Epitopic Suppressionmentioning
confidence: 81%
“…If epitope insertions can be made within AIRs without negatively influencing protein folding, it ultimately results in B cell responses being redirected away from the previous AIR and toward the introduced epitope. This concept was demonstrated by Gillam et al when they reported increased antibody titers to recombinantly inserted YSNIGVCK epitope and decreased titers to hepatitis B core antigen (HBcAg) VLP when evaluating a porcine epidemic diarrhea PBV in mice (122). A maximal insert size exists for all AIRs in which proper protein folding can still be accommodated.…”
Section: Genetic Fusion Of Bcr Epitope To Pbvmentioning
confidence: 98%
See 1 more Smart Citation
“…LGPVKLSAEGPT, TAAKTHTVRGFKV, SYFAADRLVP SAG1, GRA2, GRA7 [41] KLFETTDMY, VRQEAIARALARAAA Anopheles mosquito salivary proteins [70] GNIEGQWALKNHSLVSLSEQVLVSCDNIDD CPA (Cysteine peptidase A) [59] YSNIGVCK [71] QTLIAIHTLAIRYAN Paracoccidioides brasiliensis gp43 antigen [72] RPPIFIRRL, sSVRDRLARL EBNA3 [19] Residues 137-160 and 197-211 VP1 gene of foot-and-mouth disease virus [73] (TAKDGMEYYNKMGELYKQ, (RCLLGFKEVGGKCVPASI) Plasmodium knowlesi merozoite surface protein-142 [7] TCPDKKSTA SAG1 (59-67) [9] KSFKDILPK, STFWPCLLR, AVVSLLRLLK, SSAYVFSVK, AMLTAFFLR) SAG1, SAG2, GRA5, SRS52A, GRA6 [17] appropriate adjuvants that can be used along with epitope-based vaccination strategies and establishing optimal immunization protocols along with evaluation criteria.…”
Section: Antigen Gene Referencementioning
confidence: 99%